ANALYSIS OF TWO LANGUAGE ABILITIES (BILINGUALISM) THE BADUY PEOPLE OF BANTEN PROVINCE - Hilyatusaadah, Eneng Liah Khoiriyah, Iim Khairunnisa, Dede Imtihanudin (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2025)
Badui language is one of the regional languages ​​in Indonesia and its existence is quite well preserved by the local government, although linguistic research on this language is still relatively small. The use of the Bedouin language is considered the most important marker of tribal identity for the Bedouin community. Even though the Badui community itself is an isolated community, in fact some of them have bilingual skills, which means they can also communicate using Indonesian in their daily lives, especially when conversing with other people from outside Badui who come to their area. Therefore, The aim of this research is to identify the language skills (bilingualism) of the Baduy community and what factors cause only some Baduy people to be able to speak Indonesian. This research uses a qualitative approach with the Internet Searching data announcement technique, namely from official websites such as journals or articles. Research data analysis was carried out in three ways, namely data reduction, data presentation, drawing conclusions, and verification. Based on the results of data analysis, it can be concluded that the Baduy people have two language skills, namely Sundanese, the Banten dialect and also Indonesian.